2016
DOI: 10.1177/2325967116654651
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Operative Management of Osteochondritis Dissecans of the Capitellum

Abstract: Background:Capitellar osteochondritis dissecans (OCD) is commonly managed surgically in symptomatic adolesent throwers and gymnasts. Little is known about the impact that surgical technique has on return to sport.Purpose:To evaluate the clinical outcomes and return-to-sport rates after operative management of OCD lesions in adolescent athletes.Study Design:Systematic review; Level of evidence, 4.Methods:The PubMed, CINAHL, EMBASE, SPORTDiscus (EBSCO), and Cochrane Central Register of Controlled Trials database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 41 publications
(119 reference statements)
0
35
1
Order By: Relevance
“…One may argue whether it is valid to combine study data because of between-study variance; however, we attempted to alleviate statistical heterogeneity with the use of a random effects model. This model has been used previously in systematic reviews who pooled data from case series studies [19, 34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may argue whether it is valid to combine study data because of between-study variance; however, we attempted to alleviate statistical heterogeneity with the use of a random effects model. This model has been used previously in systematic reviews who pooled data from case series studies [19, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Proportions of donor-site morbidity were calculated for each study using the Freeman-Tukey double arcsine transformation. Subsequently, a random effects model, to account for heterogeneity across studies, was used to calculate weighted group proportions for each harvest technique, and to compare proportions between the two techniques [19, 34]. A p value <0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…5,12 Promising outcomes in terms of pain relief, elbow function, and return to sporting activities have been reported after capitellar OATS. [1][2][3]13 However, donorsite morbidity remains a problem and the subject of ongoing debate. 14,15 A systematic review performed by our research group demonstrated considerable donorsite morbidity: 7.8% after harvesting from the knee (mainly knee pain during activities) and 1.6% after harvesting from the rib (1 pneumothorax that required insertion of a chest tube).…”
Section: See Commentary On Page 3033mentioning
confidence: 99%
“…Similarly, Bexkens et al demonstrated a much lower return-to-play rate of 62% in those with advanced stage [58]. Westerman et al performed a systematic review and meta-analysis on return to sport after operative management of OCD lesions [59]. They evaluated 24 studies reporting outcomes in 492 patients.…”
Section: Surgical Outcomesmentioning
confidence: 99%